PIXEL ART STYLE CHARACTER DESIGN FOR “PANJI TALES” GAME FROM CHARACTERS DEPICTED IN JAVANESE TEMPLES BAS RELIEF - Tegar Andito (Yayasan Sinergi Widya Nusantara, 2023)
Purpose: The purpose of this research is to design main characters for pixel graphics game entitled “Panji Tales” based on characters depicted in the scenes at Javanese temples’ bas relief. Research methods: General design methods is used for this research. This method consists of identification, analysis, synthesis, and evaluation. Findings: Result of this research are character design for four main characters of the game consist of turn around view for each character. Designed characters depicts their body shapes, clothing, jewelleries, and hairstyles derived from bas relief into pixel art form. In addition to depiction in pixel art form, designed characters also adjusted to make them possible to be animated. Also, for that purpose, walk cycle animations are made as example how the characters are animated. Implications: Finalized character design will be used as guidlines for main characters’ animation in game currently being developed.